2019
DOI: 10.1002/elps.201800493
|View full text |Cite
|
Sign up to set email alerts
|

Recent studies of docking and molecular dynamics simulation for liquid‐phase enantioseparations

Abstract: Liquid‐phase enantioseparations have been fruitfully applied in several fields of science. Various applications along with technical and theoretical advancements contributed to increase significantly the knowledge in this area. Nowadays, chromatographic techniques, in particular HPLC on chiral stationary phase, are considered as mature technologies. In the last thirty years, CE has been also recognized as one of the most versatile technique for analytical scale separation of enantiomers. Despite the huge numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 137 publications
(174 reference statements)
0
56
0
Order By: Relevance
“…Indeed, this family of CSPs has demonstrated to produce successful enantioseparations for most of the reported chiral chromatography applications [1,3,[7][8][9]. Although the chiral recognition mechanism with these cellulose-and amylose-based chiral selectors are still a matter of profound debate, it is widely accepted that a sequence of "chiral grooves" hosting the polar carbamate or ester residues exists along the main chain of the helix, with the phenyl rings being projected outwards the polymer chain [1, 3,6,[10][11][12]. When mobile phases typical of the normal-phase (NP) elution mode are used, the analyte enantiomers can activate stereoselective interactions with the polar carbamate or ester groups via hydrogen bonding with the O atom and/or the NH and C=O groups, as well as dipole-dipole interaction with the C=O residue located within the above cavities [1, 3,6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, this family of CSPs has demonstrated to produce successful enantioseparations for most of the reported chiral chromatography applications [1,3,[7][8][9]. Although the chiral recognition mechanism with these cellulose-and amylose-based chiral selectors are still a matter of profound debate, it is widely accepted that a sequence of "chiral grooves" hosting the polar carbamate or ester residues exists along the main chain of the helix, with the phenyl rings being projected outwards the polymer chain [1, 3,6,[10][11][12]. When mobile phases typical of the normal-phase (NP) elution mode are used, the analyte enantiomers can activate stereoselective interactions with the polar carbamate or ester groups via hydrogen bonding with the O atom and/or the NH and C=O groups, as well as dipole-dipole interaction with the C=O residue located within the above cavities [1, 3,6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the chiral recognition mechanism with these cellulose-and amylose-based chiral selectors are still a matter of profound debate, it is widely accepted that a sequence of "chiral grooves" hosting the polar carbamate or ester residues exists along the main chain of the helix, with the phenyl rings being projected outwards the polymer chain [1, 3,6,[10][11][12]. When mobile phases typical of the normal-phase (NP) elution mode are used, the analyte enantiomers can activate stereoselective interactions with the polar carbamate or ester groups via hydrogen bonding with the O atom and/or the NH and C=O groups, as well as dipole-dipole interaction with the C=O residue located within the above cavities [1, 3,6,[10][11][12]. Besides these polar contacts, π-π stacking interactions between the phenyl groups on the CSP and an aromatic region or an unsaturated portion of the solute may play some role in chiral recognition, especially when analyses are run in the reversed-phase (RP) mode [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beer's group described a chiral selenium-containing receptor for enantiomeric discrimination of dicarboxylates [24]. Following previous studies on XB-based high performance liquid chromatography (HPLC) enantioseparations [31][32][33][34][35][36], our groups demonstrated that ChB can participate in the recognition process underlying the enantioseparation of sulfur-containing atropisomeric 4,4 -bipyridine 1 on a cellulose-based chiral stationary phase [37].…”
Section: Introductionmentioning
confidence: 89%
“…In recent years, the computational approach applied in the study of DCs has been reported in the literature as a complementary tool to HPLC analyses. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] The main goal of these theoretical works is to aid in the elucidation mechanism of chiral discrimination, as well as in the EEO, by obtaining structural and energetic parameters at the molecular level involved in the complexation process.…”
Section: Introductionmentioning
confidence: 99%